2016
DOI: 10.4102/curationis.v39i1.1575
|View full text |Cite
|
Sign up to set email alerts
|

A life uncertain – My baby’s vulnerability: Mothers’ lived experience of connection with their preterm infants in a Botswana neonatal intensive care unit

Abstract: BackgroundPreterm and low–birth weight infants are often separated from their mothers when admitted to neonatal units for stabilisation of body temperature and technological support.ObjectivesThe aim of the study was to explore and describe the lived experiences of mothers regarding care of their hospitalised preterm infants in a neonatal unit in a public hospital in Gaborone, Botswana.MethodThis study utilised a qualitative exploratory and descriptive phenomenological study design. Mothers of hospitalised pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
65
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 45 publications
2
65
0
16
Order By: Relevance
“…Expansion of access to specialized neonatal care units (NCUs) for sick and small newborns is one of the global priorities to reduce neonatal mortality [1]. Despite the tremendous bene ts of NCUs in achieving better neonatal health outcomes, studies exploring experience of parents in NCUs have shown it to be a stressful experience for families [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of access to specialized neonatal care units (NCUs) for sick and small newborns is one of the global priorities to reduce neonatal mortality [1]. Despite the tremendous bene ts of NCUs in achieving better neonatal health outcomes, studies exploring experience of parents in NCUs have shown it to be a stressful experience for families [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Infants hospitalized in the NICU might have a higher prevalence of disorganized attachment at 36-months-old compared to their typically developing peers (Pennestri et al, 2015 ). The presence of possible neurological disabilities, along with environmental stressors (high-tech medical equipment, limited interactions, prolonged mother-infant separation) have been shown to induce maternal distress including anxiety, fear, and depression (Medina et al, 2018 ; Ncube et al, 2016 ), which is associated with reduced maternal sensitivity and inadequate infant development in infants with extremely low birth weights (Gerstein et al, 2019 ; Neri et al, 2017 ). Without adequate support for the parent-infant bonding relationship during an infants’ stay in the NICU, the long-term physical, cognitive, and psycho-emotional development of the child might not be assured.…”
mentioning
confidence: 99%
“…Further, the mothers were reported to be helplessly dependent on the medical staff with no choice but to trust them (Choi & Lee, 2018 ). In previous studies, mothers who gave birth to premature infants showed a tendency to become third-party observers and tried not to interfere with the medical staff despite wanting to be actively involved in the treatment of their infants (Choi & Lee, 2018 ; Ncube et al, 2016 ). Therefore, strategic interventions focusing on building partnerships through effective communication among health care providers and vulnerable NICU families needed to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ncube, Barlow and Mayers (2016) emphasize that in the NICU, the bonds between mothers and children may be compromised and increase maternal anxiety. The premature baby who is receiving medical care is distanced from the child who was idealized throughout the pregnancy, which may cause the mother negative feelings of sadness, stress and even rejection (Wust & Viera, 2011).…”
mentioning
confidence: 99%